Microperimetric Acoustic Biofeedback Training (MABFT) in Macular Dystrophy: A Case Report: Poster Presentation - Case Report - Ophthalmologist - KARMELITA SATARI; Elfa Ali Idrus; Fikri Barran (Majalah Oftalmologi Indonesia, 2023)
Introduction : Microperimetry (MP3) measures local retinal sensitivity for retinal functional assessment and uses the result for a biofeedback training exam for low vision patients. It can relocate the preferred retinal locus to the most sensitive area from central visual field diseases. This paper is to report the MABFT effect on reading speed and visual acuity in young, low-vision macular dystrophy patients. Case Illustration : A 34-year-old Caucasian male has been diagnosed with macular dystrophy since childhood. He has difficulties reading and recognizing small items at school because of his central visual field defect. He has MABFT six times a week and reading practice at home. His best corrected visual acuity improved from 1.1 to 1.0 logMAR and his reading speed from 20 to 30 wpm with spectacles. His right eye fixation became worse, but the left eye remained unstable. Clinically, it is still not significant for the patient. His near-visual acuity remains the same. Discussion : Conclusion : Microperimetric Acoustic Biofeedback Training increases reading speed and visual acuity in low vision macular dystrophy patients.